Role of Pakistani Media in Disseminating Core National Issues and Viewers Perception - Qaiser, Abdul Rehman; Madni, Abdul Rehman; Hassan , Shajee; Amin, Salman (Asian Journal of Empirical Research, 2014)
Today media have become most powerful element of every society and its major function is to play a role as watchdog. For this present study researchers selected a survey technique to collect data from male and female viewers of the society. To collect data from a sample of 300 by using Quota sampling technique. Unit of analysis of this study was different segments of society, i.e. Reporter, Anchors, Bureaucrates, Business Men, Teachers, Students, Analyst & Other Employees. The findings showed that that majority of respondents (59%) frequently watch private channels. It was also indicated that a large proportion of respondents are more satisfied with the role of print media a similar trend was observed across all selected population groups. Respondents are more satisfied from role of print media contents. The findings also showed that a major proportion of the respondents are somewhat satisfied with the coverage of educational issues. However, a great number of the respondents are much satisfied with the coverage given to Political leaders and political issues; similarly, the significant portion of the respondents is much satisfied with the coverage given to issues related to showbiz & sports.